Transformational Leadership, Work Motivation and Employee Performance - Elsya Meida Arif; Ujang Permana; Ihsan Herlandi Putra; Elnura; Samuel PD Anantadjaya (International Journal of Economics Development Research (IJEDR), 2023)
This research aims to examine the influence of Transformational Leadership (X1), Organizational Commitment (X2) and Work Motivation (X3) on Employee Performance (Y) at the Regional Drinking Water Company in City X, both partially and simultaneously. The sample was taken from 88 employees of the City X Regional Drinking Water Company, using a saturated sampling technique. Data collection uses a questionnaire while data analysis uses Multiple Linear Regression Analysis using the SPSS version 26 program. The test results prove that Transformational Leadership has a significant effect on Employee Performance partially, Organizational Commitment has a significant effect on Employee Performance partially. Motivation has a significant effect on employee performance partially, while simultaneously Transformational Leadership, Organizational Commitment and Work Motivation have a significant effect on employee performance with a large influence of 83.4%, the remaining 16.6% is influenced by other variables.